Tafsir Sa’ādah (Kebahagiaan) dalam Surah Hud Ayat 105 - Puspita, Ismy (Lembaga Yasin AlSys, 2023)
This study examines the interpretation of Sa'adah (happiness) in surah Hud verse 105. The type of research used is library research, namely a series of activities related to data collection, reading and recording of library data, and analyzing research. The results of this study indicate that happiness is what human beings desire. From the interpretation of Sayyid Qutb, Wahbah Az-Zuhaili, Imam At-Tabari, Imam Al Qurthubi, and Hamka, the word sa'adah has the meaning of happiness that is obtained on the last day, namely happiness because of the deeds done while in the world. The way to achieve happiness (sa'ādah) is by faith and doing good deeds, obedience, piety, repentance and love for Allah SWT. The happiness that grows from how to achieve happiness is the happiness that arises from within and then is followed by the soul. And it becomes a stronghold to always live in peace. Happiness that is awakened from within is happiness that is not easily extinguished by environmental conditions that are often turbulent. We ourselves create and control happiness, not other people or the environment. Bad things happen because some people are easily sad, complain and give up. But behind it all, if someone can have a fortress, then his soul and heart will not waver. Therefore it is very important for us to seek happiness both in this world and in the hereafter.